Investigation of lens morphology and mechanical characteristics of lens capsule and lens nucleus in patients with agerelated and diabetic cataract - A. S. Tishkova; V. A. Galanzha; A. F. Cipyashyuk; A. B. Bucharskaya; G. N. Maslyakova; A. M. Burov; A. V. Skripal (Oftalʹmologiâ, 2014)
Purpose: To investigate the influence of carbohydrate metabolism on the structure and mechanical properties of the lens capsule and nucleus.Methods: Human lens pathology was studied in different forms of cataract. 220 patients with a cataract (220 eyes) were included in this study. Morphological, immunohystological and immunocytochemical investigations of lens substance (antibodies to a- (a-А and a-В), b-, g- crystallines), spectroscopic analyses of smears and morphometric analyses of slices, investigation of lens morphology and mechanical caracteristics of lens capsule and lens nucleus were performed.Results: The capsule of the lens in patients with senile cataract contains more Na+, Cl-. The capsule of the lens in patients with senile cataract contains more Ca2+, O. Mechanical strength of the capsule in the case of diabetes mellitus was lower comparatively with senile cataract in the same age groups. More significant expression of a-В and b-crystallines was found in patients with diabetes mellitus comparatively with patients with age-related cataract. Morphological features were founded in patients with cortical and nuclear forms of senile cataract and the diabetic cataract.Conclusion: During surgery (ultrasonic microcoaxial phacoemulsification) the equivalent of ultrasound was recorded. Lower density of the lens nucleus of patients with diabetes mellitus made it possible to use lower energy parameters. Using the torsion ultrasound in those cases allowed us to decrease the influence of ultrasound on eye tissues and reduce the time of achieving the maximum BCVA in the postsurgical period.